8. Alasan Uni Emirat Arab Kembali Membantu Koalisi Anti-Isis dalam Misi Balas Dendam Yordania (2014-2015) - Permana, Faiz Abi; Windiani, Reni; Wahyudi, Fendy Eko (Journal of International Relations, 2017)
ISIS is a terrorist organization created by invasion AS to Irak in 2003. Initially name asMajelis Syura Mujahidin and then join to AQI and change its name to ISIS. On 4thSeptember 2016, when NATO held meeting in Wales, AS announce about establishment acoalition to fight ISIS, called anti-ISIS coalition. 66 countries has joined into that coalition,include Uni Arab Emirates. UAE gave massive support to coalition as military andhumanitarian helps. 14th Desember 2016, has occurred an accident Jordanian pilot hasburned by ISIS military. Three days after that accident, UAE decide to stop giving assist tocoalition. But on 5th February 2015, UAE return to help the coalition by sent a squadronjet to Jordania for fight against ISIS. This research purposes to discover why UAE decideto return into coalition on 5th February. To answer that question, researcher usedneorealist paradigm and qualitative method with explanation type. Collective data whoused by researcher through interview and literature review. The result is there are manyfactors which influencing UAE behavior in coalition, that factors comes from intern andextern, because of UAE national interest, and then another factor to get some extradomestic security and regional security in Middle East.